Menggerakkan Masyarakat Desa Ngetrep dalam Pengelolaan Sampah: Mendorong Budaya Kebersihan Berkelanjutan melalui Program Sedekah Rosok - Wahyudi, Ruhan; Hosinatun, Hosinatun; Nuroini, Ihda; Azizah, Inats Fathna; Zahro, Siti Fatimatus; Sukma, Yasinta Nirani; Ramadhani, Ahmad; Muzaki, Mohammad Mufid; Ikha’a, Anadza Awaenal; Sa’djiyah, Siti Halimatuz; Idamaningati, Idamaningati; ‘Aini, Ulfa Nur; Sarif, Muhammad Maulana Alfin; Rozaq, M. Akmalul (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Environmental cleanliness in Indonesia, especially in Ngetrep Village, is a big challenge that has not been fully resolved. The Alms Rosok Program, which is implemented through a collaborative KKN between Sunan Kalijaga University and IAIN Kediri, aims to increase community involvement in waste management, as an effort to encourage a culture of sustainable cleanliness. This program invites the public to donate household waste that still has sales value, such as used bottles, cardboard and cans, which will then be sold to financially support the NU organization in the village. Methods for implementing activities include socializing the program through religious forums such as yasinan and tahlilan, distributing rubbish bags, as well as collecting and sorting rubbish by KKN students. The results of the activity show increased community participation in waste management and the creation of a cleaner and healthier environment, as well as making a positive contribution to the sustainability of cleanliness in Ngetrep Village.